Pictogramas y lenguaje oral en los niños de 4 a 5 años de la Escuela de Educación Básica 18 de Noviembre de la ciudad de Loja, periodo 2023-2024. - Guachanamá Lopez, Jenny Mariuxi (2024)
The development of language holds significant importance in human life, serving as a fundamental means of communication and fostering cognitive skills essential for personal and social growth. Therefore, the objective of this study is to determine how the use of pictograms influences the improvement of oral language skills in 4-5-year-old children at the 18 de Noviembre Primary School in Loja city during the period 2023-2024. The study used a quasi-experimental design to evaluate its effectiveness, using a mixed-methods approach for a comprehensive analysis that included both quantitative and qualitative methods. Similarly, a descriptive approach is used to describe the characteristics of the variables. In addition, the inductive-deductive and analytical-synthetic methods are used to analyze, investigate and collect research data. In the same way, the observation technique is used to collect variables, using the Navarra-Revised Oral Language Test (PLON-R) as an instrument to determine the level of oral language development in twenty-three children aged four to five years. The results show that 100% of the subjects had difficulties in phoneme articulation, limited vocabulary and inadequate understanding and expression of words for communication. Thus, in order to address the problem identified, an activity guide called "Pictohablando" is implemented, using pictograms, which reduced the problem by 83%. It can be concluded that the use of pictograms is a valuable pedagogical tool with a significant pedagogical impact, as their use contributes significantly to vocabulary enrichment, facilitating both comprehension and verbal expression, thus enabling effective and articulate communication. Keywords: Phonology, skills, infants, linguistic, morphology, pragmatics, pictograms